The triarchy of L2 learners’ emotion, cognition, and language performance: Anxiety, self-efficacy, and speaking skill in lights of the emerging theories in SLA - Ma, Yuxia (Frontiers in Psychology, 2022)
Given the bond between emotion and cognition undelying the broaden and build theory of positive emotions, the positive and negative emotions have critical roles in cognitive skills. The aim of this review was to probe into the triarchic relationship between L2 learners' cognition, emotion, and language performance, reflected in the bond between self-efficacy, foreign language anxiety, and speaking skill, in light of the main emergeing theories in the filed of SLA underpinning this relationship Moreover, the theoretical foundations, such as learners’ cognitive performances, Bandura’s self-efficacy theory, control-value theory, and positive psychology theory, were explicated in order to justify the relationship between self-efficacy and oral communication skill. Furthermore, the underlying theories such as attentional control theory, complex dynamic system theory, affective filter theory, and cultural schema theory, which relate foreign language anxiety to speaking skill were scrutinized in this review. The review also expounded the implications and future directions for EFL teachers, material designers, teacher educators, educational policy-makers, and advisors. The ideas can improve their awareness of learner self-efficacy, foreign language anxiety, and oral communication skill in educational contexts.